RELATIONSHIP BETWEEN SELF COMPASSION AND RESILIENCE AMONG ADOLESCENTS WHOSE PARENTS ARE DIVORCED - Hermansyah, Muhamad Taufik (PEOPLE: International Journal of Social Sciences, 2019)
Self-Compassion is an alternative model for self-views related to the difficult life circumtances to promote resilience among adolescents (Neff & McGehee, 2010). This study was aimed at determining the relationship between Self Compassion and Resilience among Adolescents whose parents are divorced. The study has been carried out on 36 subjects, 8 are males and 28 are females which 18-21 years old whose parents are divorced in Yogyakarta, Indonesia. The study used Self Compassion Scale (Neff, 2003) adapted by Danisati (2018) and The Connor-Davidson Resilience Scale (Connor & Davidson, 2003) developed by Septriani (2017). The study hypothesized, there was a positive relationship between self-compassion and resilience. Statistical results used the Pearson Rho technique showed that there was a significant positive relationship between self-compassion and resilience (p = 0,000, r = 0,554). The relationship between the two variables showed that the higher the Self Compassion shown by adolescent, the higher the Resilience of their life.